How does copayment for health care services affect demand, health and redistribution? A systematic review of the empirical evidence from 1990 to 2011 - Kiil, Astrid; Houlberg, Kurt (The European journal of health economics, 2014)
This article reviews the quantitative evidence on the behavioural effects of copayment within the health area across a wide range of countries. The review distinguishes itself from previous similar reviews by having a high degree of transparency for the search strategy used to identify the studies included in the review as well as the criteria for inclusion and by including the most recent literature. Empirical studies were identified by performing searches in EconLit. The literature search identified a total of 47 studies of the behavioural effects of copayment. Considering the demand effects, the majority of the reviewed studies found that copayment reduces the use of prescription medicine, consultations with general practitioners and specialists, and ambulatory care, respectively. The literature found no significant effects of copayment on the prevalence of hospitalisations. The empirical evidence on whether copayment for some services, but not for others, causes substitution from the services that are subject to copayment to the 'free' services rather than lower total use is sparse and mixed. Likewise, the health effects of copayment have only been analysed empirically in a limited number of studies, of which half did not find any significant effects in the short term. Finally, the empirical evidence on the distributional consequences of copayment indicates that individuals with low income and in particular need of care generally reduce their use relatively more than the remaining population in consequence of copayment. Hence, it is clear that copayment involves some important economic and political trade-offs.